Teacher preparation in Singapore : a concise critical history - Chia, Yeow-Tong, 1974-; Chew, Alistair; Tan, Jason, 1962- (Emerald studies in teacher preparation in national and global contexts., 2021)
Over the last two decades, the range of curricular offerings in Singapore has diversified almost beyond the ability of teacher preparation systems to cope. Teacher training has evolved from informal to formal, and from multiple 'providers' to a single institution responsible for pre-service teacher education. Teacher Preparation in Singapore is a non-celebratory and non-institution-based account of teacher preparation written with a critical academic lens. Contributing to the historiography of Singapore, as well as to the general history of teacher education, this book discusses the history of teacher preparation in Singapore from the colonial era, when Singapore was the centre of British Malaya, to the present day. It includes the pre-professional era of an informal approach to teacher education before the establishment of formal teacher training, the role of the colonial state and post-colonial state in the provision of teacher education, and issues such as policy borrowing, diffusion of educational philosophies, and developments paralleling those in the United Kingdom and elsewhere. This is a relevant and important book for researchers of education history, comparative and international education, and teacher education in Singapore.